Exploring microbial diversity, antibiotic resistance, and their environmental drivers in urban and peri-urban riverbed sediments of sub-tropical river basins - Pandey, N. K.; Simon, M.; Vishwakarma, R. K.; Sen, S.; Joshi, H.; Yadav, Shweta; Mateo-Sagasta, Javier; Jampani, Mahesh; Sikka, Alok; Hazra, S. (2026)
Rivers travel through diverse landscapes and carry natural and anthropogenic materials, which affect the dynamics of the biological and physicochemical properties of the river and riverbed sediments. Anthropological activities such as urbanization and industrialization release vast amounts of contaminants that can alter a river’s ecology and contribute to the emergence of drug resistance. This study explores two subtropical river basins in India, focusing on the main river Song (flowing through a peri-urban sub-basin) and joined by its tributaries, viz. Rispana, Bindal, and Suswa (flowing through a heavily urbanized sub-basin). A total of 27 sediment samples were collected from 9 sites in winter, summer, and monsoon seasons of the year 2024 to explore microbial diversity, antibiotic-resistant bacteria (ARB), physicochemical properties, antibiotic residues, and heavy metal concentrations. Results highlight that heavily urbanized sub-basins sediments carry more contaminants and a high load of antibiotic-resistant bacteria, ESKAPE pathogen genera, and Enterobacterales in comparison to periurban river basins. However, both sub-basins predominantly carry the bacterial phyla Pseudomonadota and Bacillota, including pathogenic genera such as Pseudomonas, Staphylococcus, and Acinetobacter. Our analysis demonstrated that elevated concentrations of heavy metals and antibiotics are closely associated with increased levels of antimicrobial resistance. Overall, this study provided comparative insights into the peri-urban and heavily urbanized sub-basin river sediments microbiome, antibiogram, and their drivers. The results and findings of this study may help to develop a basic framework of policy recommendations for better managing subtropical river basins in urbanized areas.